2002
DOI: 10.1051/0004-6361:20021490
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of calcite in the solar type protostar NGC 1333-IRAS 4

Abstract: Abstract. We present observations, obtained with ISO-LWS, of the continuum between 50-200 µm of the solar type protostar IRAS 4, in the NGC 1333 complex. The continuum presents an excess, around 95 µm, that we demonstrate must be a dust feature. We compared the 95 µm excess with the calcite feature at 92 µm and find that it fits the observations reasonably well. There may be a further contribution from hydrous silicates at ∼100 µm, but this seems a less robust result. The detected calcite mass is ∼8 × 10 −5 M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…For example, Onaka & Okada found a feature at 65 µm that may be due to diopside, a calcium-bearing crystalline silicate. Ceccarelli et al (2002c) showed that the spectral energy distribution of one protostar, NGC 1333 IRAS4, has excess emission at 95 µm, which may be ascribed to calcite-a calcium-containing carbonate. Calcite has also been found in two planetary nebulae by Kemper et al (2002) and is common in meteorites, with abundances of ∼0.3-1% of the (warm) dust mass in all types of objects.…”
Section: Crystalline Silicatesmentioning
confidence: 99%
“…For example, Onaka & Okada found a feature at 65 µm that may be due to diopside, a calcium-bearing crystalline silicate. Ceccarelli et al (2002c) showed that the spectral energy distribution of one protostar, NGC 1333 IRAS4, has excess emission at 95 µm, which may be ascribed to calcite-a calcium-containing carbonate. Calcite has also been found in two planetary nebulae by Kemper et al (2002) and is common in meteorites, with abundances of ∼0.3-1% of the (warm) dust mass in all types of objects.…”
Section: Crystalline Silicatesmentioning
confidence: 99%
“…4) To end, a broad emission feature is found at 100 µm in the Carina Nebula and Sh 171, possibly due to carbon onion grains . A similar broad feature around 90 µm is reported in evolved stars and a low mass protostar, attributed to calcite, a Cabearing carbonate mineral (Ceccarelli et al, 2002;Kemper et al, 2002).…”
Section: Pahs and Dustsupporting
confidence: 75%
“…Mid-and far-infrared spectroscopy of PMS circumstellar disks have shown some unexpected features which might be explained by X-ray heating. These include a heated layer of gas in outer disk regions (Bary et al 2003) and the possible presence of aqueous minerals in circumstellar grains (Ceccarelli et al 2002). X-ray ionization should also alter astrochemical reactions in disks (Aikawa & Herbst 2001 Finally, we note that X-ray imaging surveys are uniquely effective in locating older PMS (post-T Tauri) stars which have lost most of their accretion and disk indicators but still exhibit elevated magnetic activity.…”
Section: Magnetic Flares Circumstellar Disks and Planet Formationmentioning
confidence: 91%